Responses of laying hens to induce molting procedures using cassava meal of variable length with or without recovery period - Gongruttananun, Nirat; Saengkudrua, Kanokporn (Agriculture and Natural Resources, 2016)
The effects were determined of varying the length of the recovery period on postmolt performance in laying hens induced to molt by cassava meal. The hens were randomly assigned to one of five groups: group 1 (NC), the control group, whereas groups 2 (IM0), 3 (IM1), 4 (IM2) and 5 (IM3) were subjected to an induced molt program. The procedure included a 14 d stress period, during which the birds were induced to molt with cassava meal, and recovery periods varying from 0 wk to 3 wk. Hens in the IM0, IM1, IM2 and IM3 groups had recovery periods of 0 wk, 1 wk, 2 wk and 3 wk, respectively, during which they were fed a pullet developer diet. During the early postmolt period, the egg production of the IM0 group was significantly lower than that of the control group. The IM1 hens consumed significantly more feed and had a significantly higher feed conversion ratio than the control birds. The albumen height was significantly improved by the IM0 and IM1 treatments. No consistent differences were observed among treatments for any parameter of postmolt performances, except for improved albumen weight and mortality rate, which were observed in the IM3 group. Scanning electron microscopy illustrated evidence of erosion in the mammillary layer of the shell in the control hens. The density of the mammillary knobs in all molted groups was significantly lower than that of the control group. The mammillary knob diameter of the IM2 group was significantly greater than that of the control group.